2019
DOI: 10.3389/fped.2019.00368
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Approaches to Treating Pediatric Leukemias

Abstract: Over the past decades, striking progress has been made in the treatment of pediatric leukemia, approaching 90% overall survival in children with acute lymphoblastic leukemia (ALL) and 75% in children with acute myeloid leukemia (AML). This has mainly been achieved through multiagent chemotherapy including CNS prophylaxis and risk-adapted therapy within collaborative clinical trials. However, prognosis in children with refractory or relapsed leukemia remains poor and has not significantly improved despite great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 122 publications
2
33
0
Order By: Relevance
“…Different inhibitors of the Akt/mTOR axis have been studied in AML and demonstrated to have cytotoxic activity [ 74 ]. Inhibitors of the mTORC1 complex, the previously cited rapalogs, showed promising results, evidenced in a study conducted by treating AML primary blasts with Everolimus [ 75 ]. Nonetheless, to date, these drugs used in combination with chemotherapy in clinical trials for refractory/relapsed patients have not confirmed the expected preclinical results [ 61 ].…”
Section: Current Knowledge On Pediatric Acute Leukemiamentioning
confidence: 99%
“…Different inhibitors of the Akt/mTOR axis have been studied in AML and demonstrated to have cytotoxic activity [ 74 ]. Inhibitors of the mTORC1 complex, the previously cited rapalogs, showed promising results, evidenced in a study conducted by treating AML primary blasts with Everolimus [ 75 ]. Nonetheless, to date, these drugs used in combination with chemotherapy in clinical trials for refractory/relapsed patients have not confirmed the expected preclinical results [ 61 ].…”
Section: Current Knowledge On Pediatric Acute Leukemiamentioning
confidence: 99%
“…However, a proportion of patients still shows no response to existing therapeutic drugs and suffered from the side-effects of long-term multi-drug treatment. In addition, existing therapeutic drugs cannot further improve the prognosis of refractory and relapsed B-ALL ( Kuhlen et al, 2019 ). Therefore, new strategies for the treatment of B-ALL should be identified.…”
Section: Introductionmentioning
confidence: 99%
“…With recent advances in multi-modal chemotherapy regimens, the 5-year overall survival has reached 90% in children with B-ALL, whereas the outcome of older patients (≥40 years) remains poor (1). Moreover, the refractory and relapsed B-ALL patients show no response to existing therapeutic drugs, and a proportion of patients cannot tolerate the sideeffects of multi-drug combination therapy (2). Therefore, identifying new alternative drugs for the treatment of B-ALL is necessary.…”
Section: Introductionmentioning
confidence: 99%